DINAMIKA KOORDINASI STAKEHOLDER DALAM UPAYA MELINDUNGI PEKERJA MIGRAN INDONESIA DI KABUPATEN KARAWANG - Siti Masitoh; Dewi Noor Azijah; Lina Aryani (LPPM Universitas Abdurrab, 2025)
This study aims to analyze the synergy and coordination dynamics among stakeholders in the effort to protect Indonesian Migrant Workers (PMI) in Karawang Regency. Employing a post-positivist paradigm and a qualitative method with a case study design, data were collected through observation, interviews, and documentation. The findings reveal the absence of clear agreements and commitments among stakeholders, although there is adequate competence and awareness regarding the protection of migrant workers. The continuity of coordination depends on the presence or absence of complaints from PMI and is not bound by a predetermined schedule. The study concludes that strengthening intensive and sustainable coordination is necessary to enhance the protection of Indonesian Migrant Workers.